Exploration of enhanced recovery after surgery in female pelvic floor reconstruction: a retrospective study - Xiao, Ya; Hong, Shasha; Wan, Yuting; Tang, Jianming; Min, Jie; Hu, Ming; Li, Suting; Chen, Linxiang; Hong, Li (Frontiers in Medicine, 2025)
BackgroundPelvic organ prolapse (POP) is a prevalent condition treated with pelvic floor reconstruction surgery, which can be associated with significant postoperative morbidity. This study evaluated the safety and feasibility of an enhanced recovery after surgery (ERAS) protocol specifically for this procedure.MethodsA retrospective analysis was conducted on 80 patients undergoing POP surgery between March 2022 and March 2023; 39 were managed with the ERAS protocol and 41 received conventional care. The ERAS pathway comprised multimodal interventions across preoperative, intraoperative, and postoperative phases. Primary outcomes were postoperative length of stay (LOS) and hospitalization costs.ResultsThe ERAS group had a significantly shorter postoperative LOS (112.14 vs. 154.87 h, p < 0.001) and lower hospitalization costs (¥40,483.02 vs. ¥42,942.12, p = 0.037) than the control group. There were no 30-day readmissions or reoperations in either group. The incidence of PONV was lower in the ERAS group (2.6% vs. 19.5%, p = 0.029). Time to first flatus, first ambulation, full unassisted ambulation, and return to basic activities of daily living (ADLs) were all significantly shorter in the ERAS group (all p < 0.05), and the overall complication rate was lower. Both groups showed comparable and significant improvements in POP-Q stage and Patient Global Impression of Improvement (PGI-I) scores at 30-day follow-up, with no significant differences in VAS or Quality of Recovery-15 (QoR-15) scores between groups.ConclusionThe implementation of the ERAS protocol for pelvic floor reconstruction is safe, feasible, and effective, leading to accelerated recovery, shortened hospital stay, and reduced cost, without compromising patient safety or satisfaction. These findings support the broader adoption of ERAS in POP surgery.